OSCILLATIONS OF A TWO-LAYER PLATE UNDER IMPACT LOAD - Khadzhieva S. S. (Bright Mind Publishing, 2025)
This article examines the effect of a normal load on an infinite piecewise-homogeneous two-layer plate, when the materials of the upper and lower layers of the plate are elastic. The transverse displacement of points of the contact plane of a two-layer plate is determined, which satisfies the approximate equation obtained in [1], replacing only the viscoelastic operators with the elastic Lamé coefficients, respectively.
Keywords: Oscillation equations, two-layer plate, displacement, elastic, viscoelastic, boundary conditions, initial conditions, operator, Lamé coefficients, differential equation, Fourier integral, complex frequency.